Sources of Corporate Profits in India : Business Dynamism or Advantages of Entrenchment? - Walton, Michael (IMF Working Papers; Working Paper, 2011)
Some see India's corporate sector as the fundamental driver of recent and future prosperity. Others see it as a source of excessive market power, personal enrichment, and influence over the State, with an ultimately distorting influence. To inform this debate, this paper analyses the correlates of profitability of firms listed on the Bombay Stock Exchange, covering a dynamic period-in terms of firm entry and growth-from the early 1990s to the late 2000s. Overall, the results do not provide support for the systematic exercise of market power via the product market. At least for this period, the story is more consistent with a competitive and dynamic business sector, despite the continued dominance of business houses and public sector firms in terms of sales and assets. Those with opposing views can, with justification, argue that our analysis does not cover influences, such as corporate governance and state-corporate relations, which may paint a less flattering picture of the corporate sector's role. Those broader themes deserve further attention.